Pencemaran Udara Perkotaan dan Beban Penyakit Respiratori/Kardiopulmoner: Systematic Review Transparan, Replikatif, dan Berbasis Appraisal Kualitas Bukti - Irham Ansya; Muhammad Fachri; Nurmalia Lusida (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Urban air pollution is a modifiable environmental determinant that contributes to the burden of respiratory and cardiopulmonary diseases. The initial SLR manuscript provided a comprehensive synthesis, but it needs to be strengthened to ensure greater transparency, replicability, and a focus on evidence quality appraisal. Objective: This review synthesizes evidence from the past five years on the association between PM2.5, PM10, NO2, O3, traffic-related pollutants, and household air pollution with asthma, COPD, respiratory infections, reduced lung function, hospitalizations, mortality, DALYs, and YLLs. Methods: The review was conducted in accordance with PRISMA 2020. The search was conducted on PubMed/MEDLINE, Scopus, Web of Science Core Collection, ScienceDirect, SpringerLink, and Google Scholar on June 6, 2026, for articles published between January 1, 2021, and June 6, 2026. Duplicate removal was performed using DOI/PMID, normalized titles, and manual matching. Study quality was assessed using the JBI Critical Appraisal Tools, ROBINS-E/ROBINS-I, and AMSTAR 2, depending on the study design. Results: The workflow log aligns with the PRISMA source manuscript: 492 records, 122 duplicates, 370 records screened, 197 full-text reports assessed, 50 reports excluded, and 147 studies included. The most consistent evidence was found for PM2.5 and NO2, particularly regarding asthma/COPD hospitalizations, respiratory mortality, and cardiopulmonary burden. Ozone is more prominent in COPD and the elderly due to acute oxidative effects, impaired mucociliary clearance, and interactions with temperature and summer exposure. Household air pollution differs from ambient air pollution because microenvironmental exposure intensity is higher, exposure duration is more closely tied to domestic activities, and the burden is disproportionately borne by women, children, and low-income households. Conclusion: This systematic review indicates that controlling PM2.5, traffic-related NO₂, combustion-derived particles, ozone in the elderly and those with COPD, and household air pollution should be a priority for environmental-health policies, including in Indonesia.